Relapse in alcohol dependency and partner attitudes - Pektaş, Özkan; Mırsal, Hasan; Kalyoncu, Ayhan; Tiryaki, Ahmet; Beyazyürek, Mansur (Journal of Dependence, 2002)
Objective: There are different patterns of family behavior related to intervention and continuation of treatment and relapse prevention in alcohol dependency. In this study interrelation with relapses in alcoholism and "attitutes of partner against alcohol use" was evaluated according to the principles of behavioral family model. Method: In the study 40 male patients who relapsed after accomplishing the inpatient treatment programme compared with a control group of 40 male patients who were abstinent. All participants were married and were living with their families. The subgroups were formed according to "behavioral characteristics of the partner" as follows: behavioral enhancement of drinking; protection against the harmful effects of drinking; punishment of drinking. Statistical analysis was done on SPSS statistics programme. Results: The pretreatment attitutes of the partner of two groups are similiar (x2=3.05; df=3; p >0,05). There are statistically significant differences between posttreatment results of two groups (x2=86,0; df=3; p=0). Especially in the relapsing group "punishment of drinking" features are evident. Conclusion: The results of behavioral family model approach support that pretreatment behavioral characteristics of the partner has no effect on drinking behavior. Posttreatment altered behavioral characteristics seems to have an effect on relapse in alcohol dependency. Punishing attitutes against drinking may determine subsequent relapses.